Science Awareness and Scientific Literacy - Rennie, Leonie (2005)
The Australian Science Teachers Association (ASTA) has directed two significant projects aimed at raising science awareness in the community. The ASTA Science Awareness-Raising project and the School Community Industry Partnerships in science (SCIps) projects were funded by the Commonwealth Department of Education Science and Training as an outcome of the Commonwealth Government report entitled The Status and Quality of Teaching and Learning of Science in Australian Schools. Both projects are direct outcomes of recommendations of this report, and are based on the need for greater levels of scientific literacy in the Australian community. This article provides some background to these projects and describes, with examples drawn from ASTA journals, the nature of scientific literacy.